(untitled) (The Pakistan Development Review, 2015)
Economic and social inequality is consistently persisting in tribal region of Pakistan. People in the tribal region of Pakistan are living in deprived state whereby they lack even basic necessities in their lives. As described by Gul, the tribal areas are different than the rural areas because tribal areas are located in far flung mountainous terrain where accessibility to basic amenities is much lower than the rural areas [Gul (2013)]. In recent times, the Government of Pakistan initiated many efforts for provision of basic amenities in tribal areas as an essential component of development in the context of Millennium Development Goals (MDGs). However, according to John the desired state is yet to be achieved in tribal areas [John (2009)]. Tribal life is characterised by hardship and great insecurity especially for poor labour. Given the income vulnerabilities, the long run welfare is forgone for short run securities. Interruption, reduction or loss of earnings from the contingencies such as unemployment, underemployment, low wages, low prices and failure to find the market for the produce, old age, ill-health, sickness, disability etc. are the situations which call for social security and protection. As concluded by Talbot, this constant state of deprivation has generated deep rooted inequalities in the tribal society [Talbot (1998)]. People take rescue measures such as sending their earners to urban areas and if possible to foreign countries. Those who have lands and doing agriculture are the blessed one, although, the earning pattern is distorted due to law and order situation. To have an assessment of the overall economic inequality in the tribal region, author conducted a study in a small village Naryab which is located in the tribal region. Primary data was collected from the households physically and it was thoroughly analysed to conclude the pattern of inequality. This inequality was then mapped using latest mapping software “SURFER”.